THE IMPLEMENTATION OF SCIENTIFIC APPROACH IN TEACHING ENGLISH AT THE TENTH GRADE OF SENIOR HIGH SCHOOL 7 PADANG - Diki Atmarizon; M. Zaim (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2016)
This article aims to investigate the extent to which the implementation of Scientific Approach by English teacher who taught in tenth grade at SMAN 7 Padang. Researcher tries to see the implementation of Scientific Approach in teaching and learning process, assessment and problems faced by the English teachers in teaching and learning process using scientific approach in 2013 Curriculum. Kind of the research is descriptive method. Data of the research were taken from observation and interview. Direct observation were done to see the activities and assessments conducted by English teachers in the classroom. Then, the researchers interviewed the English teacher to know the extent to which the implementation of Scientific approach in teaching and learning processes related to observing, questioning, experimenting, associating, and communicating. Then, the problems in the teaching and learning process were identified. The results showed that 69% of the steps in the scientific approach implemented by the English teacher. However the English teachers only used 62% of assessments based on the 2013 curriculum. Atferwards, there were problems faced by English teachers in the learning process in each steps in the scientific approach in the aspect of 2013 Curriculum.Key Words: Implementation, Scientific Approach, Teaching English, 2013 CurriculumIMPLEMENTASI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN BAHASA INGGRIS PADA KELAS 10AbstrakArtikel bertujuan untuk menginvestigasi sejauh mana penerapan Pendekatan Saintifik oleh guru Bahasa Inggris yang mengajar di kelas X SMAN 7 Padang. Peneliti mencoba untuk menemukan penerapan Pendekatan Saintifik dalam proses belajar dan mengajar, penilaian dan permasalahan dalam proses belajar dan mengajar dengan menggunakan Pendekatan Saintifik pada Kurikulum 2013. Penelitian ini menggunakan metode deskriptif. Data diperoleh melalui observasi dan wawancara. Observasi langsung untuk melihat kegiatan dan penilaian yang dilakukan oleh guru Bahasa Inggris di dalam kelas. Kemudian, peneliti mengadakan wawancara dengan guru Bahasa Inggris untuk mengetahui sejauh mana penerapan Pendekatan Saintifik dalam proses belajar dan mengajar yang berkaitan dengan observing, questioning, experimenting, associating, and communicating. Kemudian, Permasalahan dalam proses belajar dan mengajar tersebut kemudian diidentifikasi. Hasil penelitian menunjukan bahwa 69% tahap-tahap pendekatan saintifik diterapkan oleh guru Bahasa Inggris. Akan tetapi dalam penilaian guru Bahasa Inggris hanya menggunakan 62% jenis penilaian berdasarkan Kurikulum 2013. Lalu, dalam proses belajar mengajar terdapat permasalahan yang dihadapi guru Bahasa Inggris di setiap langkah – langkah pada pendekatan saintifik dalam aspek Kurikulum 2013.Kata Kunci: Implementation, Scientific Approach, Teaching English, 2013 Curriculum